An Updated Meta-Analysis of the Relationship Between Helicobacter pylori Infection and the Risk of Coronary Heart Disease - Tong, Ling; Wang, Bei-Bei; Li, Fei-Hong; Lv, Shu-Ping; Pan, Fei-Fei; Dong, Xin-Jiang (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary heart disease (CHD) is one of the leading causes of mortality in the world. Although the traditional risk factors for CHD have been identified, it seems that there are still many CHD cases without these factors. Previous studies have hypothesized that Helicobacter pylori (H. pylori) infection was associated with the risk of CHD. Objective The association between H. pylori infection and the risk of CHD was studied using a systematic evaluation and meta-analysis method. Methods In order to find relevant studies, four electronic databases were systematically searched until August 2021. According to the inclusion and exclusion criteria, studies were screened and data were extracted. Under the random-effects or the fixed-effects model, the odds ratio (OR) and 95% confidence interval (95% CI) were combined. All analyses were conducted using Review Manager software (RevMan 5.4). Results Among the included studies, 2 studies were analyzed for H. pylori stool antigen test, 2 studies were analyzed for H. pylori histological staining test, 13 studies were analyzed for the anti-CagA test, and 38 studies were analyzed for the anti-H. pylori IgG test. The pooled results revealed that positive anti-H. pylori IgG was significantly associated with an increased risk of CHD (OR, 1.58; 95% CI: 1.34–1.87). Similarly, positive anti-CagA, positive H. pylori stool antigen, and positive H. pylori histological staining were significantly associated with the development of CHD with (OR: 1.33, 95% CI: 1.16–1.53), (OR: 3.50, 95% CI: 1.60–7.66), and (OR: 1.78, 95% CI: 1.12–2.83), respectively. Conclusion This meta-analysis showed that H. pylori infection increased the risk of CHD. However, more studies are needed to further investigate whether early eradication of H. pylori may reduce the morbidity of CHD.